Educação atrás das grades: a formação do professor da educação de jovens e adultos o qual atua no sistema penitenciário do Estado do Maranhão - COELHO, Ellen Josy Araujo da Silva (2017)
The problem analyzed in this study was the initial training of the EJA (Education Program for Youths and Adults) teachers, whose work in the penitentiary system of the State of Maranhão. This research, anchored in the critical study, used the qualitative methodological approach, which enabled an interpretative analysis considering the perceptions of the investigated subjects, through the theoretical contribution of Minayo (2001), Gerhardt and Silveira (2009) and Fonseca (2002). The instruments of data collection were the semi-structured interview applied to a Director and the questionnaire with both open and closed questions for nine EJA teachers who work in the School of Penitentiary in Maranhão, totalizing ten subjects interviewed. The organization of data for analysis and interpretation was carried out according to the groups of information into three categories: to education for resocialization; continuing education and the difficulties of pedagogical work; motivation and permanence of the teacher in the school. In the context of EJA and teacher training, we have the contribution of Soares (2003-2006), Maria Moura (2003), Tania Moura (2009), Haddad and Di Pierro (2000, 2015), Paiva (2003), Tanuri (2000), Fusari e Córtese (1989), Godoy (2000), Silva (2003) Ribeiro e Miranda (2009), Saviani (2008), Libâneo e Pimenta (1987, 1999), Freitas (2002), Freire (1987, 1996), and other researchers, in order to evaluate the results of the present study and theorists of this subject, as well as analysis of the Brazilian Federal Constitution of 1988, Lei de Diretrizes e Bases da Educação Nacional – 1996 (National Education Guidelines), Plano Nacional de Educação – 2014 (National Education Plan), Lei de Execução Penal – 1984 (Penal Execution Law), Diretrizes Nacionais para a Oferta de Educação nos Estabelecimentos Penais – 2009 (National Guidelines to the Offer of Education on Criminal Facilities), and other legal educational texts over the prison system. The result of the research allowed to conclude that the teachers of the EJA of the penitentiary system of Maranhão do not have initial formation that allow improvement on the prison system; promote education through personal and collective commitment; perceive educational actions as an instrument of social reintegration. They emphasize, according to the statements, the abandonment of these two institutions, the educational field and public security, which supports the development of pedagogical practice. They also reveal the desire to remain in the prison environment until the possibilities of teaching are exhausted. This work is relevant in order to develop a debate and promote actions in the context of the training of teachers of the EJA in the prison system, aiming to contribute in the process of retraction of the imprisoned for social return.